Effect of Sn4+ doping on the photoactivity inhibition and near infrared reflectance property of mica-titania pigments for a solar reflective coating. Issue 15 (15th November 2016) - Gao, Qiang; Wu, Xiaomei; Ma, Yehong; Li, Dianquan; Fan, Yueming; Du, Chang
Abstract: The influence of Sn 4+ doping on the photoactivity inhibition and near infrared reflectance property of mica-titania pigments was investigated. X-ray diffraction analysis confirmed that Sn 4+ doping promoted phase transformation from anatase to rutile. The rutile promoting effect of Sn 4+ can be ascribed to the distortion of the crystal structure of anatase after the replacement of Ti 4+ by Sn 4+ . Sn 4+ doping had a great influence on the photoactivity of mica-titania pigments. The photoactivity of mica-titania pigments was enhanced at low dopant levels, whereas its photoactivity was inhibited at high dopant levels. Remarkably, the degradation rate constant of mica-titania pigments doped with 1.0 wt% of SnCl4 was approximately 12.9% of that of the undoped sample. A possible mechanism for this effect was proposed. Moreover, the near-infrared solar reflectance of mica-titania pigments reached 0.97. An approximately 8.3 °C decrease in temperature was obtained for the inner surface of a calcium silicate board coated with mica-titania pigments. Furthermore, a solar reflective coating coloured with low photocatalytic mica-titania pigments exhibited high photostability against weathering conditions. Therefore, mica-titania pigments with high levels of the Sn 4+ dopant are excellent candidates for use in solar reflective coatings.